PENGARUH BUDAYA ORGANISASI TERHADAP LOYALITAS KERJA GURU DAN TENAGA KEPENDIDIKAN DI SMA NEGERI 1 BANGUN PURBA - Hasibuan, Nur Ziah; Seprini, Seprini; Hidayat, Hidayat (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This study aims to determine the influence of organizational culture on the work loyalty of teachers and educational staff at SMA Negeri 1 Bangun Purba. Organizational culture refers to the shared values and norms within an institution that shape the behavior and loyalty of its members. Work loyalty is crucial in enhancing performance and achieving educational goals. This research employed a quantitative approach, using questionnaires distributed to 39 respondents, consisting of teachers and educational personnel. Data were analyzed using simple linear regression analysis. The results show that organizational culture has a positive and significant effect on work loyalty. A strong organizational culture fosters a supportive work environment, increases a sense of belonging and responsibility, and encourages dedication and commitment among teachers and educational staff.